2007
DOI: 10.1080/13803610701786046
|View full text |Cite
|
Sign up to set email alerts
|

On Being Gifted, but Sad and Misunderstood: Social, emotional, and academic outcomes of gifted students in the Wollongong Youth Study

Abstract: This research examined the relationships among personality factors, social support, emotional wellbeing, and academic achievement in 65 gifted secondary students, a sample drawn from a longitudinal study of over 950 students. The research demonstrated that, compared to their nongifted peers, gifted students had significantly higher academic outcomes for all subject areas except Geography and Physical Education. Teachers rated the gifted students as being welladjusted and less likely to have behavioural or emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
1
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(66 citation statements)
references
References 66 publications
2
59
1
4
Order By: Relevance
“…Vialle, Heaven, and Ciarrochi (2007) found that gifted secondary school-aged children were less satisfied with their social support than nongifted children, indicating they experienced a lower level of well-being, but that teachers rated gifted children as having fewer emotional or behavioral problems than their nongifted peers. Several other studies found that gifted children experienced a higher level of psychological well-being than their comparable peers in multiple domains (e.g., Bain & Bell, 2004;Litster & Roberts, 2011).…”
Section: Well-being Of the Giftedmentioning
confidence: 96%
“…Vialle, Heaven, and Ciarrochi (2007) found that gifted secondary school-aged children were less satisfied with their social support than nongifted children, indicating they experienced a lower level of well-being, but that teachers rated gifted children as having fewer emotional or behavioral problems than their nongifted peers. Several other studies found that gifted children experienced a higher level of psychological well-being than their comparable peers in multiple domains (e.g., Bain & Bell, 2004;Litster & Roberts, 2011).…”
Section: Well-being Of the Giftedmentioning
confidence: 96%
“…There is an implicit convergence on what might need to be assessed in an IG individual, not only to label him or her as gifted, but also boost the probabilities of him/her realizing this IG into true accomplishments by entering a so-called "success cycle," which is characterized by an adequate balance of positive affect towards the domain in which IG is manifested such that the individual exhibits engagement with and persistence in cognitively demanding tasks, resulting in high achievement and success in the domain of IG (Aiken, 1973). In this context, a variety of non-cognitive indicators are typically considered, varying widely, from personality characteristics (Cross, 2008;Vialle, Heaven & Ciarrochi, 2007;Zuo & Tao, 2001) to thinking and learning styles (Cross, 2007;Park, Park & Ho-Seong, 2005;Sak, 2004).…”
Section: Identification Of Igmentioning
confidence: 99%
“…These significant differences among GTS may have a negative impact on the emotional, psychological, and social dimensions in gifted centers. Moreover, Vialle, Heaven, and Ciarrochi (2007) posited that negative feelings toward GTS may be a barrier for these students to make positive friendships with others and may expose them to ridicule and rejection by their peers. Furthermore, Chan (2006) confirmed that GTS may be exposed to social stress related to making friends and stress related to meeting the high expectations of their parents.…”
Section: Discussionmentioning
confidence: 99%